(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article focuses on the importance of developing of a primary school teacher’s health -saving competence in the context of fulfilling the primary school’s mission - children’ health preservation. The analysis and systematization of the scientists’ opinion on the issue under study allowed us to clarify the key definition and highlight the list of areas for improving a primary school teacher’s health-saving activity: 103 1) creation of a health-saving educational environment focused on the personal, creative and spiritual development of students (taking into account their individual needs); 2) creation of safe, psychologically comfortable conditions for the educational process; 3) usage / diffusion of innovations in pedagogical science and practice, promising pedagogical experience in creation of a preventive health-saving educational space; 3) usage / diffusion of innovations in pedagogical science and practice, forward-looking pedagogical experience in creating a preventive, healthy educational space; 4) analysis of one’s own professional and pedagogical activities with a view to achieving an educational establishment’s goals and objectives, keeping and following its rules, values and traditions; 5) self-assessment of the results of means of pedagogical influence usage to ensure the quality of the educational process; 6) self-development need’s awareness, one’s strengths and weaknesses determination, planning of activities to achieve professional development objectives; 7) monitoring and balancing one’s own physical, mental, spiritual and social health by optimizing the working time cost and energy, etc. It is noted that the study of the problem of improving the quality of the educational process participants’ activities in conditions of the development of safe and healthy educational environment is one of the areas of post-graduate education institutions’ activity, as it’s evidenced by the functioning of special units including the scientific and methodological laboratory for basic health, life safety and labour protection within them. Due to the results of the analysis of the normative documents and scientific research on the problem of improving of a primary school teacher’s health-saving activity, we have proposed a list of its main directions.